Distribution of water microbes from three different depths of Sungai Kelantan at Kuala Krai - Noorkhalilie Che Abd Aziz (2017)
A huge flood hit the Kelantan State, especially at Kuala Krai district in 2014. The flood normally hit the eastern of the Peninsular Malaysia every end of year. This natural disaster could cause changes in the environment condition and alter the ecology of the involved area. The diversity of microorganism in flood water may change due to the huge flood. By using the morphology identification method, this study shows that two types of bacteria shapes were found predominantly in the Sg. Kelantan river water in Kuala Krai. Bacteria Bacillus and Coccobacillus that were found in the river water samples were identified using the morphology observation. For the Gram Stain, Gram positive bacteria and Gram negative bacteria ware found in surface layer of the river. However, only Gram positive bacteria were found in the middle layer of river. The Gram negative bacteria were more abundant than the Gram positive bacteria at the bottom of river. By using the molecular method, this study shows the present of water microbe DNA band on the agarose gel by using the optimization of DNA extraction with standard CTAB method plus proteinase K and lysozyme. Overall the upper stream of Sg. Kelantan consists of the water microbe mostly from Gram positive bacteria with Bacillus-rod shape. However, more data of molecular bacteria are needed to be able to identify the diversity of microbe, at species level that is present in Sg. Kelantan at Kuala Krai.